Awareness and usage pattern of cosmeceuticals among undergraduate medical students and their dermatological concerns - Dinesh Kumar; Naveen K. Goel; Tanya Goel; Twisha Gupta (International Journal Of Community Medicine And Public Health, 2026)
Background: Cosmetic products have become an integral part of daily life across all age groups and socioeconomic strata. Medical students are expected to possess adequate knowledge regarding cosmetic safety and evidence-based skincare practices. Present study attempts to assess their awareness and usage pattern of cosmetic and skin care products with associated factors. Methods: A cross-sectional descriptive study was conducted during August 2025 to December 2025 among 241 undergraduate medical students using Google forms. Results: Study included 153 (63.5%) females and 88 (36.5%) males. Advertisements and social media were the primary sources of awareness regarding cosmetic products (41.9%) with significantly higher proportion of females (P=0.003). followed by. Whereas, family members (24.9%) being the second most common source and significantly higher proportion of males relied on it (p=0.005). Awareness of skincare products was 53.1% and overall user rate of these products was 41.9%, with sunscreen being the most recognized (17.8%) and frequently used (19.1%) product. Acne, blackheads, and whiteheads were the most common skincare concerns reported by 34.0% students, and cosmetic use was mainly for the purpose of treating these conditions reported by 61.8% of users. Overall, 58.1% of users experienced at least one cosmetic-related adverse reaction with no significant gender differential. Conclusions: Cosmetic use was highly prevalent among medical students mainly due to influence of social media and advertisements. More than half of the users reported cosmetic-related adverse effects. Study suggests the need to strengthen cosmetovigilance and to integrate cosmetic safety education into medical training.